The Oxford Classification predictors of chronic kidney disease in pediatric patients with IgA nephropathy - Rafaela C.G. Fabiano; Stanley A. Araújo; Eduardo A. Bambirra; Eduardo A. Oliveira; Ana Cristina Simões e Silva; Sérgio V.B. Pinheiro
Abstract Objective: The Oxford Classification for Immunoglobulin A nephropathy (IgAN) identifies pathological variables that may predict the decline of renal function. This study aimed to evaluate the Oxford Classification variables as predictors of renal dysfunction in a cohort of Brazilian children and adolescents with IgAN. Methods: A total of 54 patients with IgAN biopsied from 1982 to 2010 were assessed. Biopsies were re-evaluated and classified according to the Oxford Classification. Multivariate analysis of laboratory and pathological data was performed. The primary outcomes were decline of baseline estimated glomerular filtration rate (eGFR) greater than or equal to 50%. Results: Mean follow-up was 7.6 ± 5.0 years. Mean renal survival was 13.5 ± 0.8 years and probability of decline ≥50% in baseline eGFR was 8% at five years of follow-up and 15% at ten years. Ten children (18.5%) had a decline of baseline eGFR ≥ 50% and five (9.3%) evolved to end-stage renal disease. Kaplan-Meier analysis showed that baseline proteinuria, proteinuria during follow-up, endocapillary proliferation, and tubular atrophy/interstitial fibrosis were associated with the primary outcome. Multivariate Cox analysis showed that only baseline proteinuria (HR, 1.73; 95% CI, 1.20-2.50, p = 0.003) and endocapillary hypercellularity (HR, 37.18; 95% CI, 3.85-358.94, p = 0.002) were independent predictors of renal dysfunction. No other pathological variable was associated with eGFR decline in the multivariate analysis. Conclusion: This is the first cohort study that evaluated the predictive role of the Oxford Classification in pediatric patients with IgAN from South America. Endocapillary proliferation was the unique pathological feature that independently predicted renal outcome.